A four-season prospective study of muscle strain reoccurrences in a professional football club - Carling, C.; Le Gall, F.; Orhant, E. (Research in Sports Medicine, 2011)
The aim of this investigation was to characterise muscle strain reinjuries and examine their impact on playing resources in a professional football club. Muscle strains and reoccurrences were prospectively diagnosed over four seasons in first-team players (n = 46). Altogether, 188 muscle strains were diagnosed with 44 (23.4%) of these classed as reinjuries, leading to an incidence of 1.32 strain reoccurrences per 1,000 hours exposure (95% Confidence Interval [CI], 0.93-1.71). The incidence of recurrent strains was higher in match-play compared with training (4.51, 95% CI, 2.30-6.72 vs 0.94, 95% CI, 0.59-1.29). Altogether, 50.0% of players sustained at least 1 reoccurrence of a muscle strain, leading to approximately 3 days lost and 0.4 matches missed per player per season. The incidence of recurrent strains was highest in centre-forwards (2.15, 95% CI, 1.06-3.24), peaked in May (3.78, 95% CI, 0.47-7.09), and mostly affected the hamstrings (38.6% of all reoccurrences). Mean layoff for nonreoccurrences and recurrences was similar: -.5 days. These results provide greater insight into the extent of the problem of recurrent muscle strains in professional football.